Histochemical and Molecular Characterization of Spongiosal Cells in Native Tissue, Two- and Three-Dimensional Cultures of Rat Aortic Valve. (4th January 2016) - Nanduri, Vibudha; Moein, Beheita; Thatipalli, Avinash Raj; Pande, Gopal; Ganguly, Anasuya
Abstract : The histocytochemical and molecular analysis of cells that constitute the aortic valve (AV) of the rat heart was done in this study. We have focussed on the identity of cells in the spongiosal layer of the valve by immunofluorescence studies using lineage specific markers and cytochemical staining. We have established two-dimensional (2D) cultures of cells from isolated rat AV leaflets and maintained endothelial and interstitial valvular cells (IVC) over a period of six to eight weeks. Using "passage 0" cells from 2D valvular cultures, we could reconstruct the three-dimensional (3D) valvular tissue in collagen gels that showed very similar cellular organization and marker expression profile, as that of the native tissue. Lineage specific markers in the native tissue and cell cultures were studied by Reverse Transcriptase-PCR and immunofluorescence for VCAM-I, α -SMA, collagen I, CD71, collagen II, and E-cadherin markers. This is the first report on the identification of cell lineages in the spongiosal layer of AV and the successful reconstruction of 3D valvular tissue from primary cell cultures of AV.